Review of Burnett, Mark Thornton (2013). Shakespeare and World Cinema. Cambridge: Cambridge University Press - García Periago, Rosa María (International Journal of English Studies, 2014)
Mark Thornton Burnett’s Shakespeare and World Cinema is a valuable, more-than-welcome addition to a growing field of criticism – Shakespeare film scholarship. It is a fascinating and groundbreaking book that explores the significance of non-English language Shakespearean adaptations, drawing on examples from Africa, Brazil, India, Malaysia, Mexico, Singapore, Tibet and elsewhere. (...)